Dioxin Causes Ventral Prostate Agenesis by Disrupting Dorsoventral Patterning in Developing Mouse Prostate - Vezina, Chad M. (Oxford University Press, 2008)
Prostate ductal development is initiated by androgen-dependent signals in fetal urogenital sinus (UGS) mesenchyme that stimulate prostatic bud formation in UGS epithelium. 2,3,7,8-Tetrachlorodibenzo-p-dioxin (TCDD, 5 μg/kg maternal dose) inhibited ventral and dorsolateral but not anterior prostatic budding. We sought to determine which stage of budding, specification or initiation, was inhibited. Ventral prostatic bud formation was maximally inhibited when TCDD exposure spanned E15.5–16.5 and dorsolateral prostatic bud formation when it spanned E14.5–15.5. Because ventral and dorsolateral buds are specified at these times, TCDD impaired bud specification. We hypothesized that TCDD inhibited ventral bud specification by forming a continuous smooth muscle barrier between UGS mesenchyme and epithelium in the ventral prostatic UGS region, blocking mesenchymal-epithelial signaling, but no such barrier was found. We hypothesized that increased aryl hydrocarbon receptor (AHR) signaling in ventral and dorsolateral UGS increased their sensitivity to TCDD, but levels of AHR nuclear translocator (ARNT) protein, Ahr mRNA, and AHR-dependent gene expression were not higher than in anterior UGS where budding was unaffected. However, we identified overlapping expression of Ahr, ARNT, and AHR-induced transcripts in the periprostatic mesenchyme which intimately contacts UGS epithelium where buds are specified. This was considered the putative TCDD site of action in the UGS for inhibition of ventral and dorsolateral prostatic bud specification. Thus, hyperactivation of AHR signaling appears to disrupt dorsoventral patterning of the UGS, reprogramming where prostatic buds are specified, and prostate lobes are formed. Disrupted axial patterning provides a new paradigm for understanding how in utero TCDD exposure causes ventral prostate agenesis and may shed light on how TCDD impairs development of other organs.